1996
DOI: 10.1088/0963-9659/5/5/017
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractivity in poly(N-vinylcarbazole)-based polymer composites

Abstract: Abstract. The mechanism of photorefractivity in a family of model composites based on PVK is discussed. Novel aspects of photorefractivity that are unique in polymers are described. The effect of plasticization on their photorefractive performance is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Composite PR materials are of particular interest because the nature and concentration of each component can be independently varied to meet specific application requirements. A series of poly(N‐vinylcarbazole) (PVK)‐based PR composites have been investigated,3, 4 and it was found that the superior performance of these materials arises from an enhancement mechanism which relies on the ability of the nonlinear chromophores to reorient under the influence of the space charge field. This enhancement can be optimized with efficient plasticization and, as a result, several PR composites with diffraction efficiency approaching 100% have been reported 5–7…”
Section: Introductionmentioning
confidence: 99%
“…Composite PR materials are of particular interest because the nature and concentration of each component can be independently varied to meet specific application requirements. A series of poly(N‐vinylcarbazole) (PVK)‐based PR composites have been investigated,3, 4 and it was found that the superior performance of these materials arises from an enhancement mechanism which relies on the ability of the nonlinear chromophores to reorient under the influence of the space charge field. This enhancement can be optimized with efficient plasticization and, as a result, several PR composites with diffraction efficiency approaching 100% have been reported 5–7…”
Section: Introductionmentioning
confidence: 99%